2011
DOI: 10.1038/nsmb.2109
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of actin filament nucleation by Vibrio VopL and implications for tandem W domain nucleation

Abstract: Pathogen proteins targeting the actin cytoskeleton often serve as model systems to understand their more complex eukaryotic analogs. We show that the strong actin filament nucleation activity of Vibrio VopL depends on its three W domains and dimerization through a unique VopL C-terminal domain (VCD). The VCD displays a novel all-helical fold and interacts with the pointed end of the actin nucleus, contributing to the nucleation activity directly and through duplication of the W domain repeat. VopL promotes rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 45 publications
5
98
1
Order By: Relevance
“…An interaction of the Spir proteins with the formin FH2 dimer therefore should dimerize the Spir proteins ( Figure 1). Consistent with the findings that enforced dimerization of the N-terminal Spir-WH2 domains increases Spir nucleation activity, the interaction of a Spir-KIND-WH2 protein with a nucleation incompetent C-terminal Capu dimer markedly increased the Spir nucleation activity (Quinlan et al, 2007;Namgoong et al, 2011).…”
Section: Actin Nucleation By the Spir/fmn Complexsupporting
confidence: 70%
See 1 more Smart Citation
“…An interaction of the Spir proteins with the formin FH2 dimer therefore should dimerize the Spir proteins ( Figure 1). Consistent with the findings that enforced dimerization of the N-terminal Spir-WH2 domains increases Spir nucleation activity, the interaction of a Spir-KIND-WH2 protein with a nucleation incompetent C-terminal Capu dimer markedly increased the Spir nucleation activity (Quinlan et al, 2007;Namgoong et al, 2011).…”
Section: Actin Nucleation By the Spir/fmn Complexsupporting
confidence: 70%
“…The Spir-WH2 nucleation rate, however, was very slow compared with the Arp2/3 complex. It was later shown that enforced dimerization of the Spir-WH2 cluster strongly enhances the nucleation activity (Namgoong et al, 2011).…”
Section: Actin Nucleation By the Spir/fmn Complexmentioning
confidence: 99%
“…Despite possessing two WH2 domains, SALS-WH2 can only sequester actin monomers but cannot promote nucleation. However, the WH2 domains of SALS are similar to those found in Spire, Cordon Bleu, N-WASP or in VopL/F proteins, which sequester actin monomers, and their efficient nucleation promoting activity requires other modules surrounding the WH2 motifs (10,(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 98%
“…The presence of tandem WH2 domains can lead to a further level of functional complexity by integrating multiple activities in actin dynamics into a single protein. In vitro, tandem WH2 domains, such as found in Spire, Cordon Bleu, N-WASP, and the Vibrio cholerae/parahemeolyticus VopL/F proteins, possess monomer sequestration activity, which can be converted into nucleation and filament depolymerizationpromoting functions by other modules surrounding the WH2 domains (10,(12)(13)(14)(15)(16)(17). Additionally, the tandem WH2 domains 2 The abbreviations used are: Tmod, tropomodulin; WH2, Wiskott-Aldrich syndrome protein homology 2; Lmod, leiomodin, SALS, sarcomere length short; IAEDANS, 1,5-IAEDANS, 5-((((2-iodoacetyl)amino)ethyl)amino)naphthalene-1-sulfonic acid; Alexa488NHS, Alexa Fluorா 488 carboxylic acid succinimidyl ester; TIRFM, total internal reflection fluorescence microscopy; WIP, Wiskott-Aldrich syndrome protein-interacting protein.…”
mentioning
confidence: 99%
“…Purification tags were removed (Fig. S2B), as they can potentially affect polymerization, particularly the GST tag that induces dimerization, a factor known to increase the polymerization activity of WH2 domain-based nucleators (17). Bulk polymerization was measured using the pyrene-actin assay with 2 μM Mg-ATP-actin (6% pyrene-labeled) (18).…”
mentioning
confidence: 99%